Analisis Kualitas NaCl dan Keadaan Garam yang Dihasilkan dari Perairan Bangka Selatan - Misleni Indah Purwati; Andi Gustomi; Okto Supratman; Okto Supratman; Okto Supratman (Universitas Bangka Belitung, 2020)
This study aims to determine the quality of salt and classification of salt allotment produced from the South Bangka waters. The time and place of this research was conducted in October 2019 to January 2020 in the area of ​​South Bangka Regency which included Mempunai Beach, Puding Beach, Kubu Beach, Batu Perahu Beach and Tanjung Kemirai Beach. Sea water from the five locations was crystallized into salt using the evaporation method with the help of the fuel heat. Then the salt from the crystallization process was carried out to the laboratory analysis and organoleptic test to see the levels of NaCl and the condition of the salt which includes odor, taste and color. The results showed the quality of salt produced from the five locations based on NaCl levels was in the category of K3 salt quality with NaCl levels from each location ranged from 65.51% -75.98%. Whereas visually it falls into the K1 salt quality category for salt produced from Kubu I, Kubu III and Tanjung Kemirai beaches. Test parameters such as the smell and taste of the salt produced have met the salt quality requirements for iodized consumption salt quality requirements according to SNI 4435:2017. Overall salt quality seen from the texture of the salt produced has a smooth texture. Allotment of salt produced from the five locations, both from the level of NaCl and the quality of the odor, taste, and color, is suitable for the management of fishery products in the form of salted fish.